Wolbachia strain wAu efficiently blocks arbovirus transmission in Aedes albopictus. - Maria Vittoria Mancini; Christie S Herd; Thomas H Ant; Shivan M Murdochy; Steven P Sinkins (Public Library of Science (PLoS), 2020)
The global incidence of arboviral diseases transmitted by Aedes mosquitoes, including dengue, chikungunya, yellow fever, and Zika, has increased dramatically in recent decades. The release of Aedes aegypti carrying the maternally inherited symbiont Wolbachia as an intervention to control arboviruses is being trialled in several countries. However, these efforts are compromised in many endemic regions due to the co-localization of the secondary vector Aedes albopictus, the Asian tiger mosquito. Ae. albopictus has an expanding global distribution following incursions into a number of new territories. To date, only the wMel and wPip strains of Wolbachia have been reported to be transferred into and characterized in this vector. A Wolbachia strain naturally infecting Drosophila simulans, wAu, was selected for transfer into a Malaysian Ae. albopictus line to create a novel triple-strain infection. The newly generated line showed self-compatibility, moderate fitness cost and complete resistance to Zika and dengue infections.